INTRODUCTION OF INFORMATION TECHNOLOGIES IN THE CUSTOMS PRACTICE OF UKRAINE - MYKULIAK, Olesia; STEFANYSHYN, Roksolana (Scientific journal «World of Finance», 2020)
Introduction. International integration into the world economic community involves the mainstreaming of information technologies in the customs business. The study purpose is to analyze the regulatory and practical aspects of the functioning of electronic communications in the customs sphere of Ukraine, as well as assess the impact of information technologies on the development of Ukrainian customs practice. Methods. A number of methods are applied in the research article, including methods of critical analysis, scientific abstraction and generalization, methods of comparison etc. These methods outline and address challenges regarding the mainstreaming of information technologies into the customs practice of Ukraine. Results. The systematic introduction of electronic technologies in the Ukrainian customs system has some obstacles. The principle reason is lacking of a coherent position regarding the introduction for the electronic exchange of information with the state authorities issuing relevant permits. Moreover, the Ukrainian customs authorities do not have internal communication with the controlling authorities, that prevents the exchange of permit documents. Additionally, the issue of transition to electronic document circulation and the creation of a unified global system of “e-government” with a multitude of subsystems as well as lack of convenient access to tariff and statistical information. As the current legislation is focused on paper document circulation, there are problems with declaration and document circulation in an electronic way. Conclusions. Promising successful directions of electronic communications development in the Ukrainian customs business and raising the level of customs relations are the following ones: transparency and openness of customs clearance procedures; saving of time for customs clearance and control; minimization of opportunities for corruption; lack of subjectivity and manual interference in customs control procedures; motivation to carry out customs control in a quality manner; improvement of the business climate; automation of customs procedures of registration, checking of customs declarations in the mode of 24/7/365; distribution of declarations between inspectors automatically taking into account their workload, specializations and qualifications; in the absence of risks, automatic completion of customs clearance.